(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Production is a very important functional area in management. It has a very crucial place in every industrial organization. Opera tion management deals with the production of goods and services that people buy and use every day. Operation management deals with decision making in the production function. The trends in operation management are never fads. They have very good reasons to be in existence. They incorporate a lot of lessons from the past and can affect the future in several ways (Nersesian, 2000). From the industrial revolution in 1769 up to the recent internet revolution, Operation management has seen trends, which designed and redesigned the processes in order to make them more efficient, and business more profitable.This paper will focus on a very few of such recent trends which have come up as the need of the hour and will dictate the future of the businesses. Further the paper discuss how just in time or lean management and supply chain management influences all other trends popular in the field of operations management at the moment. This makes an interesting study as to how operations management has evolved in the face of changing businesses and the recent trends gives a very clear idea about what to expect in the near future, with respect to operations management.The paper also touches upon relevant aspects of the case of Toy ota, which have affected the way we see operations management today.